Role of Chemokines in Leishmania Infection - Roychoudhury, Kaushik; Roy, Syamal (Current Molecular Medicine, 2004)
Chemokines are a growing group of chemoattractant cytokines that play important roles in physiological as well as pathological processes. Their roles in various aspects of pathogenesis and inflammation have come to light in the past decade or so. It is becoming increasingly clear that chemokines play a major, perhaps decisive role in Leishmania infections. In this review, we recapitulate important works linking the chemokine system with relation to visceral and cutaneous leishmaniasis over the past decade and attempt to put it all together to propose a single yet unfinished model to account for all the findings.
Keywords: Leishmania